Catastrophic Healthcare Payments and Impoverishment in the Occupied Palestinian Territory - Mataria, Awad (2012)
Financial protection from the risks of ill health has globally recognized importance as a principal performance goal of any health system. This type of financial protection involves minimizing catastrophic payments for healthcare and their associated impoverishing effects. Realization of this performance goal is heavily influenced by factors related to the overall policy environment and sociopolitical context in each country. To examine the incidence and intensity of catastrophic and impoverishing healthcare payments borne by Palestinian households between 1998 and 2007. The incidence and intensity of these effects are examined within the historically unique policy and socioeconomic context of the occupied Palestinian territory. A healthcare payment was considered catastrophic if it exceeded 10% of household resources, or 40% of resources net of food expenditures. The impoverishing effect of healthcare was examined by comparing poverty incidence and intensity before and after healthcare payments. The data source was a series of annual expenditure and consumption surveys covering 1998 and 2004-7, and including representative samples of Palestinian households (n = 1231-3098, per year). Total household expenditure was used as a proxy for household level of resources; and the sum of household expenses on a comprehensive list of medical goods and services was used to estimate healthcare payments. While only around 1% of the surveyed households spent >= 40% of their total household expenditures (net of food expenses) on healthcare in 1998, the percentage was almost doubled in 2007. In terms of impoverishing effect, while 11.8% of surveyed households fell into deep poverty in 1998 due to healthcare payments, 12.5% of households entered deep poverty for the same reason in 2006. Over the same period, the monthly amount by which poor households failed to reach the deep poverty line due to healthcare payments increased from $US 9.4 to $US 12.9.The inability of the Palestinian healthcare system to protect against the financial risks of ill health could be attributed to the prevailing sociopolitical conditions of the occupied Palestinian territory, and to some intrinsic system characteristics. It is recommended that pro-poor financing schemes be pursued to mitigate the negative impact of the recurrent health shocks affecting Palestinian households.